Corporate entrepreneurship and employees' competencies: Do employees' perceived feasibility and desirability matter? - Abigail Padi; Wilberforce Owusu Ansah; Mahmoud Abdulai Mahmoud (Cogent Business & Management, 2022)
The purpose of the study was to investigate the influence of antecedents of corporate entrepreneurship (CE) on competencies of employees of Small and Medium Scale Enterprises (SMEs) in Sekondi-Takoradi Metropolis, considering the respective mediating and moderating roles of employees' perceived feasibility and desirability. A cross-sectional and descriptive survey design that makes use of quantitative approach was used. A sample of 449 employees of SMEs in the Metropolis was used. Computer method of simple random sampling technique was used to select the firms and the employees. Questionnaire was used to collect the data. Pearson product moment correlation, hierarchical multiple regression, mediation and moderation analyses were used to analyse the data. It was revealed that when employees perceive organisational and environmental factors in positive terms, they are likely to believe that they possess the necessary skills and abilities required to be successful in undertaking a task which will in turn boost the level at which they want to become an intrapreneur. It was recommended to owners/managers of SMEs to ensure that they champion innovative ideas, recognise employees who articulate good ideas, and provide the necessary resources to all employees to help boost their corporate entrepreneurial actions. This study was successful in developing an empirical model for understanding the influence corporate entrepreneurship has on employees' competencies and the mediating and moderating roles of perceived feasibility and desirability, respectively, on the relationship between CE and employees' competencies.
Keywords: 650; Environmental factors; corporate entrepreneurship competencies; organisational factors; perceived desirability; perceived feasibility